RECONCILING THE MADRASSAH WITH THE SCHOOL: Freedom of Religion, Education, and the Dilemma of Contemporary Muslims - Irfan, Ghazala (Journal of Dharma, 2006)
When we look at education today, we see that there are no inflexible dogmas and no infallible masters. Everything is to be understood in rational and human terms. There is no finished body of knowledge; the search for truth is perennial and the quest unending. The model discipline here is, of course, philosophy. Yet, this model seems to be at odds when it comes to education concerning religion. In Islam, the pivot and fulcrum of all life is Allah. Allah is ‘everywhere’ (Omni-present), ‘every when’ (eternal), ‘every what’ (Omni-competent), ‘every why’ (Omniscient), and ‘every who’ (Omni-potent). There is authoritative knowledge in religion: eternal, infinite, perfect, and complete.